REVITALIZATION OF BATAK TOBA CULTURAL IDENTITIES USED LANGUAGE AS COMMUNICATION IN THE SIANJUR MULA-MULA, SAMOSIR REGENCY (REVITALISASI IDENTITAS BUDAYA BATAK TOBA MENGGUNAKAN BAHASA SEBAGAI KOMUNIKASI DI SIANJUR MULA-MULA KABUPATEN SAMOSIR) - Ulung Napitu; Corry Corry; Bongguk Sihaloho; Yenny Mariani Napitupulu; Khalida Juniarti; Hasma Irawati Batubara (Jurnal Gramatika, 2022)
At the moment, there are indications that the Toba Batak people of Sianjur Mula-Mula District have disregarded the sociocultural values embodied in indigenous wisdom regarding the protection of Lake Toba. The deterioration of sociocultural values has increased environmental damage to Lake Toba, which is currently escalating. This study aims to examine how Toba Batak sociocultural values can be revitalized to protect the Lake Toba environment in Sianjur Mula-Mula Regency. The descriptive qualitative method with purposive sampling was used in this study. The informants interviewed using this sampling technique are individuals aware of the deterioration of Toba Batak's sociocultural values associated with the Lake Toba environment. The data analysis process begins with collecting primary data via in-depth interviews guided by interview guidelines and supplemented with library data. The interview results were compiled, tabulated, analyzed, verified, and presented for conclusions. The findings indicate that environmental damage to Lake Toba occurs due to the Toba Batak people in Sianjur Mula-Mula District largely disregarding sociocultural values and indigenous wisdom regarding environmental conservation. Therefore, preserving the environment is critical to revitalizing the Toba Batak community's sociocultural values related to environmental preservation according to contemporary needs.